Aerobic Oxidation of Isoeugenol to Vanillin with Copper Oxide Doped Reduced Graphene Oxide. Issue 10 (11th April 2017) - Bohre, Ashish; Gupta, Dinesh; Alam, Md. Imteyaz; Sharma, Rakesh K.; Saha, Basudeb
Abstract: Vanillin is a high value flavor and fragrance ingredient which is mostly sourced from synthetic route with a small fraction obtained from natural vanilla. The catalytic upgrading of biomass lignin to vanillin is of interest for sustainability and economic viability of the cellulosic biorefineries. Herein, we report reduced graphene oxide supported copper oxide (CuOx/rGO) catalyzed aerobic oxidation of lignin and clove oil derived isoeugenol to vanillin. We characterized CuOx/rGO by spectroscopic (powder XRD, FTIR, XPS, Raman) technique to elucidate active sites of the catalysts. XPS and PXRD characterizations confirm the presence of nanoparticulate crystalline CuOx in the form of mixed valence CuO and Cu2 O on the rGO surface. CuOx/rGO with 20% CuOx exhibits superior activity, enabling a maximum of 53% vanillin yield at mild reaction conditions. The catalyst retained comparable activity in the 4 th cycle. The reasons for high activity of CuOx/rGO and a plausible mechanism involving a free‐radical pathway are elucidated. Abstract : Copper doped reduced graphene oxide (CuOx/rGO) catalyzed aerobic oxidation of isoeugenol under mild reaction conditions achieved a maximum 53% yield of vanillin. The effects of critical reaction parameters on the oxidation and possible reaction pathways are elucidated.